A comparison of blood glucose and insulin responses in subjects with non-insulin dependent diabetes mellitus consuming potato alone, and potato with sunflower oil - Köseoğlu, Sabiha Zeynep Aydenk (Osman SAĞDIÇ, 2019)
Aim: The objective of this study was to compare between carbohydrate intake and carbohydrate with sunflower oil intake effects on blood glucose and insulin levels for using to plan the diets for type II diabetes mellitus. Material and method: In our study, two types of test foods were given to 10 voluntary type II diabetic patients (4 male, 6 female, mean age 50.3 ± 14.6 years and mean duration of diabetes 3.1 ± 0.3 years), and fasting and postprandial blood sugar and insulin parameters were examined and compared. As the 1st test meal: 250 grams of potato (containing 50 grams of carbohydrate) were boiled for 45 minutes, then fed to the subjects. As a 2nd test meal: after 14 days from the 1st test meal, 250 grams of potato were boiled for 45 minutes, peeled and fed in puree form with the addition of 20 ml sunflower oil. Blood samples were taken before and 30, 60, 90 and 120 minutes after the test meals, respectively. Results: When the serum glucose and insulin levels in blood samples from patients were examined, the relationship between potato alone and potato with sunflower oil co-administration was not statistically significant (p>0.05, for all times) Similarly, there was no difference in glucose areas after the 1st and 2nd test meals (p=0.562, p>0.05). There was also no significant difference in the serum insulin area after the 1st and 2nd test meals (p=0.90, p>0.05). Conclusion: There is not a difference in terms of serum glucose and insulin responses in the type II diabetic patients when they are only fed boiled potatoes, a food with high glycaemic index, compared to when the boiled potato is added 20 ml of sunflower oil. As can be understood from this study, when regulating the diet of the type II diabetic patients, it should be planned considering the glycaemic index of the food given as it is, since adding fat to the food does not affect the serum glucose and insulin response.
Keywords: Carbohydrate; Potato; Fat; Blood Glucose; Blood Insulin; Glucose response; Insulin response; Type II diabetes